2019
DOI: 10.1126/sciadv.aay2670
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA neuroLNC regulates presynaptic activity by interacting with the neurodegeneration-associated protein TDP-43

Abstract: The cellular and the molecular mechanisms by which long noncoding RNAs (lncRNAs) may regulate presynaptic function and neuronal activity are largely unexplored. Here, we established an integrated screening strategy to discover lncRNAs implicated in neurotransmitter and synaptic vesicle release. With this approach, we identified neuroLNC, a neuron-specific nuclear lncRNA conserved from rodents to humans. NeuroLNC is tuned by synaptic activity and influences several other essential aspects of neuronal developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 45 publications
1
43
0
Order By: Relevance
“…LncRNAs have been reported to exert their biological functions by interacting with certain proteins [ 30 ]. Interestingly, PVT1 was predicted to bind ATG14 using the online alignment tool RPISeq ( http://pridb.gdcb.iastate.edu//RPISeq/ ) [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…LncRNAs have been reported to exert their biological functions by interacting with certain proteins [ 30 ]. Interestingly, PVT1 was predicted to bind ATG14 using the online alignment tool RPISeq ( http://pridb.gdcb.iastate.edu//RPISeq/ ) [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence indicates that lncRNAs play key roles in gene regulation and disease processes. 1 , 2 , 3 , 4 , 5 , 6 It has been demonstrated that lncRNAs mediate gene regulation through binding with DNA, RNA, or proteins. 7 , 8 , 9 , 10 For example, lncRNAs may act as signals or decoys of transcription, as protein scaffolds, or as epigenetic regulators.…”
Section: Introductionmentioning
confidence: 99%
“…Forty percent of described lncRNAs have been reported in the CNS [102], where they participate in gene expression, imprinting and pluripotency regulation, as reported by numerous studies [103][104][105][106]. One of the first described lncRNAs was H19, a paternally imprinted gene, whose importance in embryonic development and neural viability has been established [107].…”
Section: Long Non-coding Rnasmentioning
confidence: 99%
“…NeuroLNC, a nuclear lncRNA, has been recently involved in synapsis establishment. Its interaction with the well-known RNA-binding protein TDP-43 appears to be essential for the correct release of neurotransmitters [106]. In addition, RMST1 functions as a guide-RNA for SOX2 transcription factor towards neurogenic genes [110] promoting neural differentiation although it is also expressed in astrocytes [111].…”
Section: Long Non-coding Rnasmentioning
confidence: 99%